2013
DOI: 10.5114/kitp.2013.34309
|View full text |Cite
|
Sign up to set email alerts
|

REHABILITATION Functional testing of muscles in patients with pectus excavatum – indications for preoperative rehabilitation

Abstract: Introduction: Studies of people with pectus excavatum usually relate to physiological abnormalities caused by the deformity, as well as its impact on posture. Little is known about muscle length disorders associated with this defect. Aim of the study: Determining whether the presence of pectus excavatum is associated with changes in muscle length; developing guidelines for preoperative rehabilitation of pectus excavatum patients. Material and methods: 19 patients aged 13-19 years with diagnosed pectus excavatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…It means that external and internal forces that affect the function of the respiratory muscles will also affect postural responses 13 . It has been previously shown that the flexibility of muscles such as the pectoralis major and the internal rotators of humeral joints is greater in PE patients 11 . So it may be an important factor leading to a decrease in PS among PE patients when compared to healthy controls 41 , 50 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It means that external and internal forces that affect the function of the respiratory muscles will also affect postural responses 13 . It has been previously shown that the flexibility of muscles such as the pectoralis major and the internal rotators of humeral joints is greater in PE patients 11 . So it may be an important factor leading to a decrease in PS among PE patients when compared to healthy controls 41 , 50 .…”
Section: Discussionmentioning
confidence: 98%
“…PE is often observed in children with muscular disorders, such as in children with Marfan syndrome, Ehlers-Danlos syndrome, osteogenesis imperfecta, or homocystinuria 3 , 5 . It is also known that patients with PE who are free of such diseases have greater flexibility of some muscles compared to healthy controls 11 . The muscles of the chest which are affected by PE are mainly respiratory muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Это влечёт ухудшение качества жизни пациентов, проявляющееся снижением выносливости при физической нагрузке, затрудненным дыханием, одышкой, болью в груди [5]. В настоящее время стали появляться свидетельства нарушения стабильности осанки у больных с воронкообразной деформацией грудной клетки [6]. Детальное изучение вертикального баланса у таких пациентов необходимо для лучшего понимания сложного механизма функционирования их органов и систем.…”
Section: Conflict Of Interestunclassified